Communist parties in the Middle East 100 years of history - Izquierdo, Ferran (Europa regional perspectives, 2019)
The book has been designed to offer a unique, updated and comprehensive study of Communist parties in the Middle East, based on a theoretical framework of analysis, substantial empirical research and archive documentation